2020
DOI: 10.12911/22998993/122119
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Indicators of Surface Waters of the Tatra National Park

Abstract: The study examines selected physical and chemical indicators of water at four sites in the Tatra National Park and one in Zakopane. The results were compared with the requirements to be met by water intended for human consumption. On the basis of the analyses, the examined samples of water were assessed in terms of their potential use as potable water supplies for the human population. It was found that water collected from selected intake points meets the standards for the tested physical and chemical indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Until 1991, Lake Z was an upper Jurassic limestone quarry, and a 2003 study by Galas [ 49 ] reported high conductivity and chloride content of water due to infiltration from the nearby Vistula River. Lake M was reported to have a cadmium concentration of about 0.13 mg/dm 3 due to anthropogenic activities [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Until 1991, Lake Z was an upper Jurassic limestone quarry, and a 2003 study by Galas [ 49 ] reported high conductivity and chloride content of water due to infiltration from the nearby Vistula River. Lake M was reported to have a cadmium concentration of about 0.13 mg/dm 3 due to anthropogenic activities [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tourism may also be affecting water quality in the region. Sobczyk et al ( 2020 ) noted the potentially large ecological impact of mass uncontrolled tourism on the region. Tourism development and visitation of the mountains has increased in recent years (Getzner & Švajda 2015 ).…”
Section: Introductionmentioning
confidence: 99%